Effect of counterface roughness on the friction of bionic wall-shaped microstructures for gecko-like attachments. (4th August 2017) - Kasem, Haytam; Cohen, Yossi
Abstract: Hairy adhesive systems involved in gecko locomotion have drawn the interest of many researchers regarding the development of bionic solutions for fast and reversible adhesive technologies. To date, despite extensive efforts to design gecko-inspired adhesive surfaces, adhesion and friction capacities are often evaluated using smooth and rigid counterfaces, in general glass, whereas most natural and artificial surfaces inevitably have a certain level of roughness. For that reason, in this study experiments tested the effects of the substrate roughness on the friction of bionic wale-shaped microstructures for gecko-like attachments. To this end, 12 substrates with different isotropic roughness were prepared using the same Epoxy material. Friction force was measured under various normal loads. It was concluded that classical roughness parameters, considered separately, are not appropriate to explain roughness-related variations in friction force. This has led us to develop a new integrative roughness parameter that combines characteristics of the surface. The parameter is capable of classifying the obtained experimental results in a readable way. An analytical model based on the experimental results has been developed to predict the variation of the friction force as a function of counterface roughness and applied normal load.